Veterans Health Administration : Dr. Kizer considers radical surgery on an ailing system - Mitkowski, Allison; Feinstein, Jonathan S., 1960- ([London] : SAGE, 2016)
As a navy diver and an emergency room physician, Dr. Kenneth Kizer had faced pressure-filled situations requiring focus and determination. As the director of the California Department of Health Services, he had proven his ability to navigate a bureaucracy, and had built a reputation for orchestrating major improvements using a no-nonsense approach to managing healthcare. In 1994, as the newly-appointed director of the Veteran's Health Administration (VHA), the doctor knew he would have to draw on his past experiences as he faced the most formidable challenge of his career. This case study examines this topic.
Originally Published in: Mitkowski, A., & Feinstein, J. (2007). Veterans Health Administration: Dr. Kizer Considers Radical Surgery on an Ailing System. 07-017. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Kizer, Kenneth W; Health services administration -- United States -- Case studies; Organizational change -- Management -- Case studies